The effect of tri hita karana culture in relationship between work stress and internal auditor performance - Aditya, A.A. Gde Dwi; Kusuma, Made Gede Wira (International research journal of management, IT and social sciences, 2019)
The purpose of this study was to obtain empirical evidence regarding the effect of work stress on auditor performance, and Tri Hita Karana's cultural ability to moderate the effect of work stress on auditor performance. The technique of determining the sample used is the nonprobability sampling method with a purposive sampling technique. The questionnaire is used as a method of data collection. The questionnaire is used as a method of collecting data sent to the internal auditors of Rural Banks (BPR). Of the 51 questionnaires distributed to all BPRs in Badung Regency, 43 questionnaires were feasible to analyze, with a questionnaire return rate of 94 percent and a questionnaire level that could be used at 84 percent. The hypothesis was tested at a 5 percent significance level using the Absolute Difference Value Test. The hypothesis was tested at a significance level of 5 percent using the Absolute Difference Value Test with the SPSS program. The output of the research instrument testing shows that the instrument has passed the validity and reliability test, and has fulfilled the classical assumption test requirements.